General practitioners' use of absolute risk versus individual risk factors in cardiovascular disease prevention: an experimental study. Issue 5 (15th May 2014) - Jansen, Jesse; Bonner, Carissa; McKinn, Shannon; Irwig, Les; Glasziou, Paul; Doust, Jenny; Teixeira-Pinto, Armando; Hayen, Andrew; Turner, Robin; McCaffery, Kirsten
Abstract : Objective: To understand general practitioners' (GPs) use of individual risk factors (blood pressure and cholesterol levels) versus absolute risk in cardiovascular disease (CVD) risk management decision-making. Design: Randomised experiment. Absolute risk, systolic blood pressure (SBP), cholesterol ratio (total cholesterol/high-density lipoprotein (TC/HDL)) and age were systematically varied in hypothetical cases. High absolute risk was defined as 5-year risk of a cardiovascular event >15%, high blood pressure levels varied between SBP 147 and 179 mm Hg and high cholesterol (TC/HDL ratio) between 6.5 and 7.2 mmol/L. Setting: 4 GP conferences in Australia. Participants: 144 Australian GPs. Outcomes: GPs indicated whether they would prescribe cholesterol and/or blood pressure lowering medication. Analyses involved logistic regression. Results: For patients with high blood pressure: 93% (95% CI 86% to 96%) of high absolute risk patients and 83% (95% CI 76% to 88%) of lower absolute risk patients were prescribed blood pressure medication. Conversely, 30% (95% CI 25% to 36%) of lower blood pressure patients were prescribed blood pressure medication if absolute risk was high and 4% (95% CI 3% to 5%) if lower. 69% of high cholesterol/high absolute risk patients were prescribed cholesterol medication (95% CI 61% to 77%) versus 34% of high cholesterol/lower absolute risk patients (95% CI 28% to 41%). 36% of patients with lower cholesterol (95% CI 30% to 43%) were prescribed cholesterol medication if absolute risk was high versus 10% if lower (95% CI 8% to 13%). Conclusions: GPs' decision-making was more consistent with the management of individual risk factors than an absolute risk approach, especially when prescribing blood pressure medication. The results suggest medical treatment of lower risk patients (5-year risk of CVD event <15%) with mildly elevated blood pressure or cholesterol levels is likely to occur even when an absolute risk assessment is specifically provided. The results indicate a need for improving uptake of absolute risk guidelines and GP understanding of the rationale for using absolute risk.